2008
DOI: 10.1037/0278-7393.34.4.859
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control and lexical access in younger and older bilinguals.

Abstract: Ninety-six participants, who were younger (20 years) or older (68 years) adults and either monolingual or bilingual, completed tasks assessing working memory, lexical retrieval, and executive control. Younger participants performed most of the tasks better than older participants, confirming the effect of aging on these processes. The effect of language group was different for each type of task: Monolinguals and bilinguals performed similarly on working memory tasks, monolinguals performed better on lexical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
793
10
18

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 657 publications
(890 citation statements)
references
References 92 publications
(106 reference statements)
69
793
10
18
Order By: Relevance
“…However, most phonological and phonetic sociolinguistic studies focused on how individual backgrounds affect specific variants, while the current study explored how individual backgrounds affect the general mechanisms which control the alignment of two tonal systems. The cognitive effects are related to previous findings on bilinguals (Bialystok et al, 2008(Bialystok et al, , 2014Signorelli et al, 2011). However, the effect of auditory working memory on the strength of systematic correspondence is relatively new.…”
Section: Main Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…However, most phonological and phonetic sociolinguistic studies focused on how individual backgrounds affect specific variants, while the current study explored how individual backgrounds affect the general mechanisms which control the alignment of two tonal systems. The cognitive effects are related to previous findings on bilinguals (Bialystok et al, 2008(Bialystok et al, , 2014Signorelli et al, 2011). However, the effect of auditory working memory on the strength of systematic correspondence is relatively new.…”
Section: Main Findingssupporting
confidence: 65%
“…Few studies have shown the relevance of auditory working memory in speech production. Even bilinguals seem to be similar to monolinguals in auditory working memory (Bialystok et al, 2008) and simultaneous interpreters seem to have no advantage in retaining auditory information (Signorelli et al, 2011). However, would auditory working memory influence the systematic correspondence shown in the bilinguals' production?…”
Section: Individual Backgroundsmentioning
confidence: 96%
“…All Chinese and Belgian participants were bilingual (i.e., Chinese and English vs. Flemish and French/English) whereas only half of the Canadian participants were bilingual (i.e., English and French). It has been shown that bilinguals have an advantage over monolinguals in nonlinguistic tasks involving executive control (e.g., Bialystok, Craik, & Ryan, 2006;Bialystok, Craik, Klein & Viswanathan, 2004;Bialystok, Craik, & Luk, 2008). Because complex arithmetic problem Complex Arithmetic -21 solving relies on executive control (see DeStefano & LeFevre, 2004, for review), bilinguals' higher level of executive control might have contributed to their strategy efficiency.…”
Section: Cultural Differences In Strategic Performancementioning
confidence: 99%
“…Older bilinguals typically show better executive function (EF) performance than their monolingual peers (Bialystok et al, 2008; see Bialystok and Craik, 2010 for a review). The bilingual participants in these studies had used both languages actively on a daily basis since childhood, so had accumulated a considerable amount of experience in manipulating both languages.…”
Section: Introductionmentioning
confidence: 99%